MECHANICAL PERFORMANCE OF POLYPROPYLENE FIBRE REINFORCED MORTAR INCORPORATING PALM OIL FUEL ASH - Raudhah, Ahmadi; Mohd Syukry, Saiful; Idawati, Ismail; Mohammad, Abdul Mannan; Ahmed, Abdullahi; Norsuzailina, Mohamed Sutan (Penerbit UMT, 2022)
The performance of Fibre Reinforced Mortar (FRM) mixed with microfine size Palm Oil Fuel Ash was investigated in this study (POFA). The ideal volume of POFA and fibre in the mixed mortar is calculated in order to generate a cost-effective high-strength mortar with increased ductility. In this experimental investigation the polypropylene fibre used ranged from 0 kg/m3 to 20 kg/m3 and the replacement of cement with microfine POFA content of 0% and 40% (optimum) was studied. The mechanical properties of fibre reinforced masonry in the presence of the POFA was tested using compressive strength, flexural and split tensile tests. The surface morphology of the fibre reinforced mortar was studied using scanning electron microscopy (SEM) which showed the good fibre-mortar bond in the morphology of the samples at 7 and 28 days. From the compressive strength results, FRM tester contains 40% microfine POFA as a replacement against cement mixed with 10 kg/m3 of polypropylene fibre is optimum and achieved compressive strength up to 79.5 MPa at the 56th day of curing. Ductility ratio up to 13.3 was achieved from the flexural test for FRM sample with 15 kg/m3 polypropylene fibres. The high strength FRM with inclusion of POFA as supplementary cementitious material had the potential to become a new sustainable material in construction.